Self-assembly of cholesterol end-capped polymer micelles for controlled drug delivery - Gao, Ming (J Nanobiotechnology, 2020)
BACKGROUND: During the past few decades, drug delivery system (DDS) has attracted many interests because it could enhance the therapeutic effects of drugs and reduce their side effects. The advent of nanotechnology has promoted the development of nanosized DDSs, which could promote drug cellular uptake as well as prolong the half-life in blood circulation. Novel polymer micelles formed by self-assembly of amphiphilic polymers in aqueous solution have emerged as meaningful nanosystems for controlled drug release due to the reversible destabilization of hydrophobic domains under different conditions. RESULTS: The amphiphilic polymers presented here were composed of cholesterol groups end capped and poly (poly (ethylene glycol) methyl ether methacrylate) (poly (OEGMA)) as tailed segments by the synthesis of cholesterol-based initiator, followed by atom transfer radical polymerization (ATRP) with OEGMA monomer. FT-IR and NMR confirmed the successfully synthesis of products including initiator and polymers as well as the Mw of the polymers were from 33,233 to 89,088 g/mol and their corresponding PDI were from 1.25 to 1.55 by GPC. The average diameter of assembled polymer micelles was in hundreds nanometers demonstrated by DLS, AFM and SEM. The behavior of the amphiphilic polymers as micelles was investigated using pyrene probing to explore their critical micelle concentration (CMC) ranging from 2.53 × 10(−4) to 4.33 × 10(−4) mg/ml, decided by the balance between cholesterol and poly (OEGMA). Besides, the CMC of amphiphilic polymers, the quercetin (QC) feeding ratio and polarity of solvents determined the QC loading ratio maximized reaching 29.2% certified by UV spectrum, together with the corresponding size and stability changes by DLS and Zeta potential, and thermodynamic changes by TGA and DSC. More significantly, cholesterol end-capped polymer micelles were used as nanosized systems for controlled drug release, not only alleviated the cytotoxicity of QC from 8.6 to 49.9% live cells and also achieved the QC release in control under different conditions, such as the presence of cyclodextrin (CD) and change of pH in aqueous solution. CONCLUSIONS: The results observed in this study offered a strong foundation for the design of favorable polymer micelles as nanosized systems for controlled drug release, and the molecular weight adjustable amphiphilic polymer micelles held potential for use as controlled drug release system in practical application.